2015
DOI: 10.1007/s40292-015-0096-1
|View full text |Cite
|
Sign up to set email alerts
|

Middle and Long-Term Impact of a Very Low-Carbohydrate Ketogenic Diet on Cardiometabolic Factors: A Multi-Center, Cross-Sectional, Clinical Study

Abstract: IntroductionObesity is a constantly growing illness in developed countries and it is strictly related to cardiovascular (CV) diseases, i.e. the main cause of mortality throughout industralised areas.Aimto test the ability of trained general physician to safely and effectively prescribe a very-low carbohydrate ketogenic (VLCK) diet in clinical practice, with a specific attention to the effect of this approach on overweight related CV risk factors (anthropometric measures) blood pressure, lipid levels, glucose m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
45
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(58 citation statements)
references
References 25 publications
4
45
1
1
Order By: Relevance
“…Incorporated exercise training has no additional effects on weight loss, but has additional benefits on cardiorespiratory fitness, and HIIT is more time efficient than the traditional MICT (2.5 min vs. 30 min).Nutrients 2019, 11, 3051 2 of 15 (LCs). Emerging evidence mainly derived from western countries has clearly shown that LCs could be effective dietary strategies for weight loss and the management of several common and rare pathological conditions [7][8][9][10][11][12][13]. A meta-analysis has revealed that LCs had greater long-term effects on weight loss when compared to the traditional low-fat diets; furthermore, triglycerides, high-density lipoprotein cholesterol (HDL-C), and blood pressure values were also more favorably altered in LCs [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporated exercise training has no additional effects on weight loss, but has additional benefits on cardiorespiratory fitness, and HIIT is more time efficient than the traditional MICT (2.5 min vs. 30 min).Nutrients 2019, 11, 3051 2 of 15 (LCs). Emerging evidence mainly derived from western countries has clearly shown that LCs could be effective dietary strategies for weight loss and the management of several common and rare pathological conditions [7][8][9][10][11][12][13]. A meta-analysis has revealed that LCs had greater long-term effects on weight loss when compared to the traditional low-fat diets; furthermore, triglycerides, high-density lipoprotein cholesterol (HDL-C), and blood pressure values were also more favorably altered in LCs [7].…”
mentioning
confidence: 99%
“…A meta-analysis has revealed that LCs had greater long-term effects on weight loss when compared to the traditional low-fat diets; furthermore, triglycerides, high-density lipoprotein cholesterol (HDL-C), and blood pressure values were also more favorably altered in LCs [7]. Additionally, LC-induced weight loss is generally accompanied with several positive metabolic changes, including improvements in blood pressure, glycaemic control, insulin sensitivity, and serum concentrations of C-reactive protein and certain lipids [8][9][10][11][12], which may have the potential to alleviate the features of metabolic disorder and reduce the risk factors associated with developing CVD and T2D. However, limited studies have tested whether LCs are also useful and feasible for the large Chinese overweight/obese population [11,13] given that people in China and in Western countries have distinct dietary patterns and preferences [14,15], which may lead to different levels of acceptance toward LCs.…”
mentioning
confidence: 99%
“…Feinman and Fine 25 state that weight loss may be related to the use of protein as an energy source, which is a process with greater energy expenditure in relation to the normal physiological process. Some studies also mention that weight loss can be attributed to reduced appetite due to the increased satiety provided by proteins 16 , to the action of ketone bodies on the direct suppression of appetite 6 , or reduced lipogenesis and increased lipolysis 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on this reasoning, from the 17 studies, eight assessed the ketogenic diet at medium and long-terms (from three months to two years) by associating it with other periods of Mediterranean diet or another type of diet balanced in nutrients 8,9,12,13,18,19,20,21 . In these studies, there was significant weight loss, reduced body fat and BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation